PENGARUH APLIKASI KOMPOS GRANUL DENGAN PEREKAT LIAT TERHADAP SIFAT KIMIA REGOSOL - Ulfia Fadilla; G Gusnidar; Syafrimen Yasin (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Regosol has low fertility, especially carbon (C), nitrogen (N), phosphorus (P), potassium (K) and other macro elements, but it can be potential for agriculture cultivation. Addition of straw compost and tithonia granule (Kojeto granule) with clay binder can improve chemical soil fertility. This study aimed to determine the composition of the Kojeto granule with a clay binder and to define the interaction between type of Kojeto granule and dosage of compost granule in the chemical characteristics of Regosol. This research was conducted in a wirehouse and soil laboratory, Andalas University. The experiment used a completely randomized factorial design, with two factors and three replications. The first factor was the ratio between compost composition and clay binder 9:1 and 8:2. The second factor was 4 levels of granule compost doses (0; 7,5; 15; 22,5 t ha-1). The results showed that the best composition ratio between Kojeto and clay binder on chemical properties was 9:1. The type of Kojeto 8:2 and dosage (22 t ha-1) had an interaction on Ca-dd (3.75 me 100 g-1). The single effect on the type compost granule at type 9:1 was parameter C-org (2.23%), and single effect on increasing the dosage of granule compost at a dose of 15 t ha-1 was C-org (2.30%), N-tot (0.27%), P-available (14,30 ppm), pH (5,80), and K-dd (0.62 me 100 g-1). The optimal recommended dose is 15 t ha-1.